Artisan bread in five minutes a day : the discovery that revolutionizes home baking - Hertzberg, Jeff (St. Martin's Press, 2007)
An accessible resource to making artisan breads at home with a minimum of time and effort counsels home bakers on how to prepare larger quantities of dough for use as needed, in a volume of recipes that also features an array of baked desserts.